Interview with Mrs. Mª Isabel Celaá Diéguez, Minister of Education and Vocational Training of Spain - Cabrera Delgado (coord.), José Manuel; Faci Lucia, Fernando; Alcalá Ibañez, Lourdes; Cuadrado Muñoz, Francisco; Morillas Molina, Laura (Avances en Supervisión Educativa, 2021)
Isabel Celaá Diéguez has a degree in Philosophy and Letters in the specialty of English Philology, a degree in Law and professor of Baccalaureate in the specialty of English. She has been a teacher for several years; She has held many different elected positions with which she has accumulated extensive management experience, preferably focused on the field of Education. She is currently Minister of Education and Vocational Training of the Government of Spain since June 7, 2018. In her mandate, Organic Law 3/2020, of December 29, has been approved, which modifies Organic Law 2/2006, of May 3, Education, also called LOMLOE and in some areas known as the Celaá law.Recently, she has presented to the Council of Ministers in first reading the text of the Draft Organic Law for the Organization and Integration of Vocational Training.The editorial team of the magazine “Advances in Educational Supervision” wanted to know first-hand the response to different concerns raised by the new law, but not without first congratulating it for having obtained its approval.